PENGARUH KEPEMIMPINAN DAN KOMUNIKASI TERHADAP PRODUKTIVITAS KERJA PEGAWAI KEPOLISIAN RESOR KUTAI TIMUR - -, LISNA WATI (EKONOMIA, 2017)
The aim of the research as follows : 1) to find out the leadership has positive and significant influence foward working productiving of staffs of east kuta resort police. 2) To find out the communication has positive and significant influence foward working productiving of staffs of east kuta resort police. 3) to find out the leadership and commnication has positive and significant influence foward working productiving of staffs of east kuta resort police.This research is quantitative research, where as the collected data resources is in number. The collected data in the research is conducted by spreading questionnaires to 75 respondents. The analysis method used in the research is multiple linier regression method. The result of linier equivalence is Y = 0,432 + 0,332. X1 + 0,590X2. From the equivalance it shows that X1 and X2 influences positirely and significantly. It means higher the leadership and communication level higher the working productivities results. The research shows that there is positive and significant influence between leadership and communication with determinant coefisient value 0,874 or 87% which means the leadership and communication influence 87% increase the working produtivity at East Kutai Resort Police.